Inhibition of O-acetylserine sulfhydrylase by fluoroalanine derivatives - Nina Franko; Konstantinos Grammatoglou; Barbara Campanini; Gabriele Costantino; Aigars Jirgensons; Andrea Mozzarelli (Taylor & Francis Group, 2018)
O-acetylserine sulfhydrylase (OASS) is the pyridoxal 5'-phosphate dependent enzyme that catalyses the formation of L-cysteine in bacteria and plants. Its inactivation is pursued as a strategy for the identification of novel antibiotics that, targeting dispensable proteins, holds a great promise for circumventing resistance development. In the present study, we have investigated the reactivity of Salmonella enterica serovar Typhimurium OASS-A and OASS-B isozymes with fluoroalanine derivatives. Monofluoroalanine reacts with OASS-A and OASS-B forming either a stable or a metastable α-aminoacrylate Schiff's base, respectively, as proved by spectral changes. This finding indicates that monofluoroalanine is a substrate analogue, as previously found for other beta-halogenalanine derivatives. Trifluoroalanine caused different and time-dependent absorbance and fluorescence spectral changes for the two isozymes and is associated with irreversible inhibition. The time course of enzyme inactivation was found to be characterised by a biphasic behaviour. Partially distinct inactivation mechanisms for OASS-A and OASS-B are proposed.